1975
DOI: 10.1002/1097-0142(197504)35:4<1230::aid-cncr2820350430>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second tumors in survivors of childhood cancer

Abstract: A new malignancy was diagnosed in 19 of 414 long-term survivors of cancer in childhood. All but two lesions were attributable to prior radiotherapy; eight were successfully treated. Excluding 4 patients ascertained in connection with the second malignancy, there were 15 in the series who developed a new cancer, in contrast to 0.7 cases expected (p less than 0.001). The 20-year (5-24 years after initial diagnosis) cumulative probability of a second cancer was 12% (S.E. 4%), and the radiation-related cancer rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
9

Year Published

1977
1977
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(64 citation statements)
references
References 21 publications
0
55
0
9
Order By: Relevance
“…Actuarial rates have ranged from 3-13% at 20 -30 years of follow-up. 6,8,10,18,22,[25][26][27] Higher rates are associated with single-institution studies, as is ours, whereas lower rates are associated with larger studies involving multiple institutions. Additional reasons may account for the higher risk estimate in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actuarial rates have ranged from 3-13% at 20 -30 years of follow-up. 6,8,10,18,22,[25][26][27] Higher rates are associated with single-institution studies, as is ours, whereas lower rates are associated with larger studies involving multiple institutions. Additional reasons may account for the higher risk estimate in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Although a genetic predisposition for cancer and previous chemotherapy may be contributing causes to the development of SNs, 5 various reports have highlighted the significant contribution of radiotherapy to the development of SNs in childhood cancer survivors. 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18] A radiation dose-effect relationship has been noted for some SNs such as bone sarcomas. 15 Children are particularly susceptible to the carcinogenic effects of radiation, possibly due to the increased rapidity of cell division in various tissues associated with the normal growth and development process.…”
mentioning
confidence: 99%
“…With this cohort, and excluding basocellular carcinomas of the skin, Tucker, for the Late Effect Study Group (LESG), found a constant standardised incidence ratio of 16, in agreement with our estimation of 13 (Tucker et al, 1984). Li, studying 410 5-year survivors from the Sidney Farber Cancer Institute, found a standardised incidence ratio of 20, not significantly different from our estimation (Li et al, 1975;Li, 1977). However, standardised incidence ratios by time periods after FPC diagnosis were not published.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these prior studies did not include patients with a primary diagnosis of AML, while others did not distinguish the primary diagnosis of ALL from that of AML. [17][18][19][20][21][22][23][24] We found only four studies that reported the number of patients with a primary diagnosis of AML who were in the cohort; either no second cancer or only one second cancer was reported for these four studies with a small number of patients (38 to 163 patients). [25][26][27][28] Comparison of the findings of these four studies with those of our study is not possible because information about the person-years at risk or the cumulative incidence of second cancer in the survivors of AML was not reported.…”
Section: Leukemiamentioning
confidence: 92%